Resistance to a nonselective 4-hydroxyphenylpyruvate dioxygenase-inhibiting herbicide via novel reduction-dehydration-glutathione conjugation in Amaranthus tuberculatus - Concepcion, Jeanaflor Crystal T (The New phytologist, 2021)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.